2023
DOI: 10.7759/cureus.36885
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-Lymphocyte Ratio (NLR) Useful as a Cost-Effective Preliminary Prognostic Marker in ST-Elevation Myocardial Infarction (STEMI): An Observational Study From a Tertiary Care Hospital in Northeast India

Abstract: IntroductionMyocardial infarction, a major consequence of coronary artery disease, is an important cause of in-hospital mortality and morbidity worldwide. Blood neutrophil-to-lymphocyte ratio (NLR) is a novel laboratory marker of systemic inflammation that can predict the severity and mortality in various non-cardiovascular illnesses, including malignancy and infective pathology. We sought to evaluate its potential in predicting the outcome in hospitalized patients with myocardial infarction. Material and meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Furthermore, NLR and anemia were independent risk factors for mortality in breast cancer patients [ 30 ]. Elevated NLR combined with decreased Hb predicted the onset of major adverse cardiovascular events in patients with ST-elevation myocardial infarction [ 14 ]. Taken together, it appears that NLR is most appropriate for following up and managing anemia associated with chronic disease rather than screening or diagnosing anemia at the population level; yet, further longitudinal studies are certainly warranted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, NLR and anemia were independent risk factors for mortality in breast cancer patients [ 30 ]. Elevated NLR combined with decreased Hb predicted the onset of major adverse cardiovascular events in patients with ST-elevation myocardial infarction [ 14 ]. Taken together, it appears that NLR is most appropriate for following up and managing anemia associated with chronic disease rather than screening or diagnosing anemia at the population level; yet, further longitudinal studies are certainly warranted.…”
Section: Discussionmentioning
confidence: 99%
“…In a study involving a Saudi population, NLR ratio was found to be an important tool in determining COVID-19 clinical status [ 12 ]. NLR is also an emerging marker in patients with heart failure, acute coronary syndrome, hypertension, and diabetes [ 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, a meta-analysis of 17 studies suggested that high NLR was associated with severity of CAD and could be useful for predicting severe stenosis [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lymphocytes, as part of the adaptive immune response, are important elements of the immunoregulatory pathway. Recently, several studies have found that an elevated neutrophil count and low lymphocyte count are closely related to the progression of atherosclerosis, or ischemia-reperfusion injury after revascularization of acute myocardial infarction [ 32 , 33 ]. Platelets are the initiating factors of thrombosis.…”
Section: Discussionmentioning
confidence: 99%